PENERAPAN UNSUR TINDAK PIDANA MELAKUKAN PENJUALAN BARANG TIDAK SESUAI DENGAN SPESIFIKASI BARANG DALAM KEMASAN OLEH PELAKU USAHA (STUDI PADA SUBDIT I INDAGSI DITRESKRIMSUS POLDA SUMBAR) - Sugama, Yoga (UNES Law Review, 2020)
The case of fraudulent acts, especially the problem of the contents in the packaging that is not in accordance with what is described in the packaging label is regulated in Article 382 of the Criminal Code. One of them is handled by the West Sumatra Regional Police's Ditreskrimsus. This is in accordance with the Police Report Number: LP/303/A/XI/2019/Spkt-Sbr, November 4, 2019, with the alleged criminal act intentionally including or making statements or statements that are misleading or not in accordance with the actual conditions or incorrect item label found on Tuesday, October 1, 2019. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. From the results of the research and discussion it can be concluded that: First, the elements of a criminal act of selling goods not in accordance with the specifications of goods in packaging by business actors in Sub-Directorate I of the Directorate General of Criminal and Criminal Investigation of the West Sumatra Regional Police, are: Article 144 Jo Article 100 paragraph (2) of Law Number 18 of 2012 concerning Food, and Article 62 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection. Second, the application of the elements of a criminal act of selling goods that are not in accordance with the specifications of packaged goods by business actors in Sub-Directorate I of the Directorate General of Criminal and Criminal Investigation of the West Sumatra Regional Police is Article 144 Jo Article 100 paragraph (2) of Law Number 18 of 2012 concerning Food, by looking at a) Anyone, b) Intentionally, and c) provide information or statements that are untrue or misleading on labels. As well as Article 62 paragraph (1) of Law Number 8 Year 1999 concerning Consumer Protection, with the following elements: a) not in accordance with the conditions; b) guarantee, features or efficacy; and c) as stated in the label, etiquette or description of the goods and / or services. Third, the obstacles encountered by the Subdit I Indagsi Ditreskrimsus Polda West Sumatra, are internal constraints and external constraints. There are internal obstacles: a) political intervention that makes this case stop; and b) given SP3. Meanwhile, the external constraints are: a) The modus operandi of the perpetrator is always changing; b) officials from related institutions who are less cooperative; and c) lack of socialization to the community, the efforts made in overcoming the obstacles have been adjusted to the needs of external and internal constraints`